Martensitic stainless steel, martensitic stainless steel member and method for manufacturing the same

The development of a martensitic stainless steel with a specific composition and manufacturing process addresses the challenge of achieving high strength and toughness while reducing the use of expensive elements, resulting in a cost-effective and performance-enhanced material.

JP7647373B2Active Publication Date: 2025-03-18DAIDO STEEL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021101265
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-18
Publication Date
2025-03-18
Estimated Expiration
2041-06-18

AI Technical Summary

Technical Problem

Martensitic stainless steels used in various applications face challenges in achieving a balance between strength, toughness, and cost, particularly when requiring high toughness, as they often contain expensive elements like Ni and Mo, and may have insufficient strength or toughness depending on the tempering process.

Method used

A martensitic stainless steel composition with specific ranges of C, Si, Mn, Ni, Cr, Mo, Nb, and V, satisfying the relationship Mo+2Nb+V≧0.08mass%, is developed, along with a manufacturing method involving quenching and tempering to achieve high strength and toughness while reducing the content of expensive elements.

Benefits of technology

The proposed martensitic stainless steel achieves high strength and toughness levels, with a hardness of 27HRC or higher and absorbed energy of 50J or more, while minimizing the use of expensive elements, thus addressing the cost and performance balance in martensitic stainless steels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647373000001
    Figure 0007647373000001
Patent Text Reader

Abstract

To provide martensitic stainless steel having a low content of expensive elements and excellent in strength and toughness, a member made of the same, and a manufacturing method thereof.SOLUTION: Martensitic stainless steel contains 0.10≤C≤0.25 mass%, 0.10≤Si≤1.00 mass%, 0.10≤Mn≤1.50 mass%, 1.00≤Ni≤3.00 mass%, 14.00≤Cr≤17.50 mass%, 0.01≤Mo≤0.40 mass%, 0.01≤Nb≤0.30 mass%, 0≤V≤0.50 mass%, and the balance of Fe and inevitable impurities and satisfies Mo+2Nb+V≥0.08 mass%. A member made of the martensitic stainless steel has a hardness of 27 HRC or more and an adsorption energy of 50 J or more. Such the member is obtained by hardening, tempering, and finishing a raw material made of the martensitic stainless steel.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a martensitic stainless steel, a martensitic stainless steel member and a manufacturing method thereof, and more particularly to a martensitic stainless steel having excellent strength and toughness, a member made of such a martensitic stainless steel, and a manufacturing method thereof. [Background technology]

[0002] Martensitic stainless steel is a Cr-based steel that is quenched from the austenite region to form a martensite structure and then tempered at an appropriate temperature before use. Martensitic stainless steel is generally hard and has excellent corrosion and wear resistance, so it is used for thin-walled components such as bearings and blades, or components with complex shapes such as screws and fuel injection system parts. Martensitic stainless steel is usually adjusted to the desired hardness and corrosion resistance by performing heat treatment such as quenching after processing into the desired shape.

[0003] Regarding such martensitic stainless steel, various proposals have been made in the past. For example, Patent Document 1 states: (a) containing prescribed amounts of C, Cr, Si, Mn, Ni, N, P, S, and Mo, with the balance being Fe and unavoidable impurities; (b) Cr-12C+0.75Ni+10N≧13.0; and (c) The δ-ferrite phase is 10% or less. A martensitic stainless steel for oil wells is disclosed. The same document states: (A) When Cr-12C+0.75Ni+10N is 13.0 or more, the corrosion rate decreases significantly, and (B) When the δ-ferrite phase is reduced to 10% or less, the impact properties and room temperature strength are improved. is stated.

[0004] Patent Document 2 discloses a martensitic stainless steel containing predetermined amounts of C, Si, Mn, P, S, Cu, Ni, Cr, Mo, V, Al, Ti, O, and N, with the balance being Fe and unavoidable impurities. The document describes that by reducing the contents of Si, Al, and Ti and adding V, it is possible to ensure temper hardness, improve corrosion resistance and cold workability, and ensure toughness.

[0005] As described above, martensitic stainless steel has high strength and is used in various applications, such as fuel injection system parts for automobiles. However, as the use environment becomes more diverse in recent years, strength and corrosion resistance may become problematic. In such cases, martensitic stainless steel containing Ni, which has excellent strength and corrosion resistance, is used. As such martensitic stainless steel, for example, EN1.4418 steel (16Cr-5Ni-1Mo) and EN1.4057 steel (0.15C-16Cr-2Ni) are known.

[0006] In particular, when toughness is required, EN1.4418 steel, which has a low carbon content, or twice-tempered EN1.4057 steel may be used. However, EN1.4418 steel is expensive because it contains a lot of Ni and Mo. In addition, EN1.4057 steel that has been tempered twice is low cost but may lack strength, while EN1.4057 steel that has been tempered once can ensure strength but may have reduced toughness. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Special Publication No. 07-026180 [Patent Document 2] JP 2005-344184 A Summary of the Invention [Problem to be solved by the invention]

[0008] An object of the present invention is to provide a martensitic stainless steel which has a low content of expensive elements and is excellent in strength and toughness. Another object of the present invention is to provide a member made of such martensitic stainless steel and a method for producing the same. [Means for solving the problem]

[0009] In order to solve the above problems, the martensitic stainless steel according to the present invention comprises: 0.10≦C≦0.25mass%, 0.10≦Si≦1.00mass%, 0.10≦Mn≦1.50mass%, 1.00≦Ni≦3.00mass%, 14.00≦Cr≦17.50mass%, 0.01≦Mo≦0.40mass%, 0.01≦Nb≦0.30mass%, and 0≦V≦0.50mass% The balance is Fe and unavoidable impurities. The relationship of the following formula (1) is satisfied. Mo+2Nb+V≧0.08mass% …(1) However, when V is not included, calculation is performed assuming V=0 in formula (1).

[0010] The martensitic stainless steel is 0.01≦V≦0.50mass% It is preferred that:

[0011] The martensitic stainless steel member according to the present invention has Made of the martensitic stainless steel according to the present invention, Hardness is 27HRC or more. The absorbed energy is 50J or more.

[0012] The manufacturing method of the martensitic stainless steel member according to the present invention comprises: a first step of manufacturing a material made of the martensitic stainless steel according to the present invention; a second step of quenching the material from a temperature equal to or higher than point A c3 and lower than the solidus temperature; a third step of tempering the quenched material; and a fourth step of finishing the tempered material to obtain a martensitic stainless steel member. It is provided with these steps.

[0013] The third step preferably includes: (a) a step of tempering at a temperature T lower than point A and equal to or higher than 400°C, or c3 (b) a step of performing the first tempering at a temperature T1 equal to or higher than point A1 and lower than point A, and then performing the second tempering at a temperature T2 (<T1) equal to or higher than 300°C and lower than point A. (b) a step of performing the first tempering at a temperature T1 equal to or higher than point A1 and lower than point A, and then performing the second tempering at a temperature T2 (<T1) equal to or higher than 300°C and lower than point A. c1 (b) a step of performing the first tempering at a temperature T1 equal to or higher than point A1 and lower than point A, and then performing the second tempering at a temperature T2 (<T1) equal to or higher than 300°C and lower than point A. c3 (b) a step of performing the first tempering at a temperature T1 equal to or higher than point A1 and lower than point A, and then performing the second tempering at a temperature T2 (<T1) equal to or higher than 300°C and lower than point A. c3 (b) a step of performing the first tempering at a temperature T1 equal to or higher than point A1 and lower than point A, and then performing the second tempering at a temperature T2 (<T1) equal to or higher than 300°C and lower than point A. It is preferably included.

Advantages of the Invention

[0014] When a predetermined amount of Mo and Nb are added in combination to martensitic stainless steel having a predetermined composition, the tempering softening resistance increases. Further, when a predetermined amount of V is added in combination in addition to Mo and Nb, the tempering softening resistance further increases. Therefore, when martensitic stainless steel having such a composition is quenched and tempered under appropriate conditions, high strength and high toughness can be obtained. In particular, when the first tempering is performed at a relatively high temperature T1 and then the second tempering is performed at a relatively low temperature T2, high strength and high toughness can be achieved in a high dimension. This is presumably because the martensite newly generated during the cooling process after the first tempering is appropriately tempered during the second tempering.

Embodiments for Carrying Out the Invention

[0015] An embodiment of the present invention will be described in detail below. [1. Martensitic stainless steel] [1.1. Main constituent elements] The martensitic stainless steel according to the present invention contains the following elements, with the balance being Fe and unavoidable impurities. The types of added elements, their component ranges, and the reasons for their limitations are as follows:

[0016] (1) 0.10≦C≦0.25mass%: C is an interstitial element and contributes to improving strength. C also improves temper hardness by combining with Cr, Mo, Nb, and / or V, which will be described later. Furthermore, C is an austenite stabilizing element, suppressing the formation of δ-ferrite phase and improving toughness. To obtain such effects, the C content must be 0.10 mass% or more. The C content is preferably 0.13 mass% or more.

[0017] On the other hand, if the C content is excessive, the formation of Cr carbides reduces the amount of dissolved Cr in the matrix, leading to deterioration of oxidation resistance. In addition, the formation of coarse primary carbides deteriorates the cold workability and toughness after solution treatment. Furthermore, the amount of retained austenite increases, leading to a decrease in tempered hardness. Therefore, the C content must be 0.25 mass% or less. The C content is preferably 0.20 mass% or less.

[0018] (2) 0.10≦Si≦1.00mass%: Si is a deoxidizing element. If the amount of Si is too small, deoxidization during melting becomes insufficient, and the cleanliness decreases. The decrease in cleanliness leads to a decrease in toughness and ductility. In order to obtain the effect as a deoxidizing element, the amount of Si must be 0.10 mass% or more. The amount of Si is preferably 0.30 mass% or more.

[0019] On the other hand, if the Si content is excessive, it is not only harmful during casting but also significantly reduces toughness and ductility. Therefore, the Si content must be 1.00 mass% or less. The Si content is preferably 0.70 mass% or less.

[0020] (3) 0.10≦Mn≦1.50mass%: Mn combines with S to improve hot workability. Mn is also effective as a deoxidizer. To obtain such an effect, the Mn content must be 0.10 mass% or more. The Mn content is preferably 0.50 mass% or more.

[0021] On the other hand, if the Mn content is excessive, the amount of retained austenite increases, leading to a decrease in tempered hardness. Moreover, excessive Mn leads to a decrease in corrosion resistance. Therefore, the Mn content must be 1.50 mass% or less. The Mn content is preferably 1.00 mass% or less.

[0022] (4) 1.00≦Ni≦3.00mass%: Ni is a strong austenite stabilizing element, which suppresses the formation of δ-ferrite phase and improves toughness. Ni also contributes to improving corrosion resistance and toughness of martensite matrix. In order to obtain such effects, the Ni content must be 1.00 mass% or more. The Ni content is preferably 1.60 mass% or more, and more preferably 2.00 mass% or more.

[0023] On the other hand, if the Ni content is excessive, the amount of retained austenite increases, resulting in a decrease in tempered hardness. Therefore, the Ni content must be 3.00 mass% or less. The Ni content is preferably 2.50 mass% or less.

[0024] (5) 14.00≦Cr≦17.50mass%: Cr is an element effective in improving oxidation resistance and corrosion resistance. In addition, Cr combines with C during tempering and contributes to improving hardness. In order to obtain such effects, the Cr content must be 14.00 mass% or more. The Cr content is preferably 15.00 mass% or more.

[0025] On the other hand, excessive Cr content promotes the formation of δ-ferrite phase, reducing toughness. Excessive Cr also increases the amount of retained austenite, reducing hardness. Therefore, the Cr content must be 17.50 mass% or less. The Cr content is preferably 17.00 mass% or less.

[0026] (6) 0.01≦Mo≦0.40mass%: Mo is an element effective for improving corrosion resistance. Mo also combines with C to form carbides during tempering, contributing to improvements in hardness and toughness, and temper softening resistance. Furthermore, Mo improves strength as a solid solution strengthening element. To obtain such effects, the Mo content must be 0.01 mass% or more. The Mo content is preferably 0.05 mass% or more.

[0027] On the other hand, an excessive amount of Mo leads to an increase in costs. Therefore, the amount of Mo must be 0.40 mass% or less. The amount of Mo is preferably 0.30 mass% or less, and more preferably 0.20 mass% or less.

[0028] (7) 0.01≦Nb≦0.30mass%: Nb combines with C during tempering to form carbides, which contributes to improving hardness and toughness, and improving temper softening resistance. In order to obtain such effects, the Nb content must be 0.01 mass% or more. The Nb content is preferably 0.03 mass% or more.

[0029] On the other hand, if the Nb content is excessive, a large amount of oxides and nitrides may remain in the steel, which may lead to deterioration of toughness. Furthermore, if the Nb content is excessive, it will lead to an increase in cost. Therefore, the Nb content must be 0.30 mass% or less. The Nb content is preferably 0.10 mass% or less.

[0030] [1.2. Inevitable impurities] "Inevitable impurities" refers to trace elements that are mixed in from raw materials and refractories during the production of stainless steel. Examples of inevitable impurities include: (a) P of 0.040 mass% or less; (b) S of 0.030 mass% or less; (c) 0.20 mass% or less of Al; (d) 0.01 mass% or less of O; (e) 0.10 mass% or less of N; (f) Cu: 0.30 mass% or less etc.

[0031] P is an element that reduces hot workability, grain boundary strength, and toughness / ductility, so the less the better. The P content is preferably 0.03 mass% or less. However, reducing the P content more than necessary leads to an increase in costs. It is preferable to select an optimal P content taking these points into consideration.

[0032] S is an element that reduces corrosion resistance, toughness and ductility during cold working, and hot workability, so the less the better. The S content is preferably 0.010 mass% or less. However, reducing the S content more than necessary leads to an increase in costs. It is preferable to select an optimal value for the S content, taking these points into consideration.

[0033] [1.2. Sub-constituent elements] The martensitic stainless steel according to the present invention may further contain the following elements in addition to the above-mentioned main constituent elements. The types of the added elements, their component ranges, and the reasons for their limitations are as follows.

[0034] (8) 0≦V≦0.50mass%: The V content may be 0 mass%. However, V combines with C to form carbides during tempering, contributing to improvements in hardness and toughness, and temper softening resistance. V also contributes to improvements in toughness as a solid solution element. To obtain such effects, the V content is preferably 0.01 mass% or more. The V content is more preferably 0.05 mass% or more.

[0035] On the other hand, if the V content is excessive, a large amount of oxides and nitrides may remain in the steel, which may lead to deterioration of toughness. Furthermore, if the V content is excessive, it may lead to an increase in cost. Therefore, the V content is preferably 0.50 mass% or less. The V content is more preferably 0.25 mass% or less.

[0036] [1.4. Ingredient balance] The martensitic stainless steel according to the present invention must satisfy the following formula (1). Mo+2Nb+V≧0.08mass% …(1) However, when V is not included, calculation is performed assuming V=0 in formula (1).

[0037] Mo, Nb, and V are elements that form carbides and contribute to improving hardness and toughness, and improving temper softening resistance. To obtain such effects, Mo+2Nb+V is preferably 0.08 mass% or more. Mo+2Nb+V is more preferably 0.20 mass% or more. As long as formula (1) is satisfied, V may be 0 mass % or may exceed 0 mass %.

[0038] [2. Martensitic stainless steel components] The martensitic stainless steel member according to the present invention is made of the martensitic stainless steel according to the present invention. The martensitic stainless steel member according to the present invention preferably has a hardness of 27HRC or more and an absorbed energy of 50J or more.

[0039] [2.1. Martensitic stainless steels] The martensitic stainless steel member according to the present invention (hereinafter, simply referred to as "member") is made of the martensitic stainless steel according to the present invention. Details of the martensitic stainless steel are as described above, and therefore will not be described here.

[0040] [2.2. Hardness and absorbed energy] The member according to the present invention is used in a quenched and tempered state, as described below. In this case, the hardness (i.e., strength) and absorbed energy (i.e., toughness) of the member mainly depend on the composition of the martensitic stainless steel and the tempering conditions. Furthermore, tempering may be performed once or twice, as described below. A material that has been tempered once generally has high hardness but low absorbed energy. On the other hand, a material that has been tempered twice has a slightly lower hardness but high absorbed energy compared to a material that has been tempered once with the same composition.

[0041] The achievable hardness and absorbed energy vary depending on the material composition and tempering conditions. For example, when a hardened component is tempered once, the hardness is usually 30 to 40HRC and the absorbed energy is 30 to 50J. On the other hand, when a hardened member is tempered twice, the hardness is usually 25 to 35 HRC and the absorbed energy is 40 to 150 J. In particular, when tempering twice, by optimizing the material composition and tempering conditions, it is relatively easy to obtain a member with a hardness of 27 HRC or more and an absorbed energy of 50 J or more.

[0042] [2.3. Shape] In the present invention, the shape of the member is not particularly limited. Furthermore, the term "member" in the present invention includes not only a final product having a specific shape, but also a semi-finished product having a shape suitable for manufacturing a final product. Examples of materials include: (a) Automotive fuel injection system parts, (b) Marine shafts; (c) aircraft parts; etc.

[0043] [3. Manufacturing method of martensitic stainless steel components] The method for producing a martensitic stainless steel member according to the present invention comprises the steps of: A first step of producing a material made of the martensitic stainless steel according to the present invention; The above material is A c3A second step of quenching from a temperature above the Ms point and below the solidus temperature, a third step of tempering the quenched material, and a fourth step of finishing the tempered material to obtain a martensitic stainless steel member are provided.

[0044] The third step is (a) a step of tempering at a temperature T above 400°C and below the A c3 point, or (b) a step of performing a first tempering at a temperature T1 above the A c1 point and below the A c3 point, and then performing a second tempering at a temperature T2 (<T1) above 300°C and below the A c3 point is preferably included.

[0045] [3.1. First Step] First, a material made of martensitic stainless steel according to the present invention is manufactured (first step). In the present invention, the method for manufacturing the material is not particularly limited, and an optimal method can be selected according to the purpose. The material is generally (a) melting and casting raw materials blended to have a predetermined composition, (b) performing ingot breakdown forging or ingot breakdown rolling on the obtained ingot to break the casting structure and at the same time making the ingot into a billet shape, (c) performing hot forging or hot rolling on the billet to obtain a material having a predetermined shape, (d) annealing the material after hot working for crack prevention as necessary is manufactured thereby.

[0046] [3.2. Second Step] Next, the material is quenched from a temperature above the Ms point and below the solidus temperature (second step). The quenching temperature is the A c3 point or higher and below the solidus temperature. The quenching temperature is the A c3There are no particular limitations on the quenching temperature, so long as it is equal to or higher than the solidus temperature (the temperature at which ferrite completes transformation into austenite when heated). In the case of the martensitic stainless steel according to the present invention, the quenching temperature is preferably 800 to 1200°C.

[0047] After the material is held at the quenching temperature for a predetermined time, the material is cooled. In the present invention, the cooling method of the material is not particularly limited. Examples of the cooling method include water cooling, oil cooling, air blast cooling, and furnace cooling (slow cooling). The martensitic stainless steel according to the present invention has high hardenability, so that a material with a diameter of about 5 cm can be sufficiently hardened even when slowly cooled.

[0048] [3.3. Third step] Next, the material after quenching is tempered (third step). The tempering conditions are not particularly limited, and it is preferable to select the optimum conditions depending on the purpose. In addition, tempering may be performed only once or may be performed twice.

[0049] [3.3.1. Tempering once] A method in which tempering is performed only once has a slightly lower absorbed energy, but is an effective method for obtaining a component with high hardness (strength). In this case, if the tempering temperature T is too low, the tempering effect is small and the absorbed energy may be low. Therefore, T is preferably 400° C. or higher. T is more preferably 500° C. or higher.

[0050] On the other hand, if T becomes too high, austenite is generated during heating and martensite is transformed during cooling, which may result in a decrease in absorbed energy. c3 T is preferably less than the point. More preferably, T is 850° C. or less. When tempering is performed once, T is particularly preferably from 500°C to 850°C.

[0051] The tempering time is not particularly limited, and an optimal time can be selected depending on the purpose. The tempering time is usually about 1 hour to 6 hours.

[0052] [3.3.2. Twice tempered] Although the method of tempering twice has a slightly lower hardness (strength) than the method of tempering once, it is an effective method for obtaining components with high absorbed energy. In particular, tempering twice is preferable for obtaining components with a hardness of 27HRC or more and an absorbed energy of 50J or more.

[0053] [A. First tempering conditions] The first tempering is performed mainly to temper the martensite formed during quenching. Therefore, if the first tempering temperature T1 is too low, the tempering effect is small and the absorbed energy may be low. Therefore, T1 is set to A c1 It is preferable that T1 is equal to or higher than the temperature at which austenite begins to form during heating. T1 is more preferably 650°C or higher. On the other hand, if T1 is too high, austenite is generated during heating and martensite is transformed during cooling, which may result in a decrease in absorbed energy. c3 It is more preferable that T1 is less than the temperature point. When tempering is performed twice, T1 is preferably 650 to 850°C.

[0054] The first tempering time is not particularly limited, and an optimal time can be selected depending on the purpose. The tempering time is usually about 1 hour to 6 hours. After the first tempering is completed, the material is temporarily cooled to a temperature of 300° C. or less.

[0055] [B. Second tempering conditions] In the case of the martensitic stainless steel according to the present invention, the hardness does not decrease much and the absorbed energy does not increase much in the first tempering. This is thought to be because austenite is partially generated when the steel is heated to the first tempering temperature T1, and new martensite is generated from the austenite during the cooling process after tempering. On the other hand, if the material is tempered a second time at a temperature T2 lower than T1 after the first tempering, the hardness decreases moderately and the absorbed energy increases significantly. This is thought to be because the martensite formed during the first tempering is tempered moderately during the second tempering.

[0056] If the second tempering temperature T2 is too low, the tempering effect is small and the absorbed energy may be low. Therefore, T2 is preferably 300° C. or higher. T2 is more preferably 400° C. or higher, and further preferably 500° C. or higher. On the other hand, if T2 is too high, austenite is generated during heating and martensite is transformed during cooling, which may result in a decrease in absorbed energy. c3 It is more preferable that T2 is 750° C. or less. When tempering is performed twice, T2 is preferably 500 to 750°C.

[0057] The second tempering time is not particularly limited, and an optimal time can be selected depending on the purpose. The tempering time is usually about 1 hour to 6 hours.

[0058] [3.4. 4th step] Next, the tempered material is finish-machined (fourth step), thereby obtaining the martensitic stainless steel member according to the present invention. The finishing method is not particularly limited, and an optimal method can be selected depending on the purpose. Examples of the finishing method include cutting and cold working.

[0059] [4. Effect] When a certain amount of Mo and Nb is added to a martensitic stainless steel having a certain composition, the tempering softening resistance increases. Furthermore, when a certain amount of V is added to Mo and Nb, the tempering softening resistance increases further. Therefore, when a martensitic stainless steel having such a composition is quenched and tempered under appropriate conditions, high strength and high toughness can be obtained. In particular, when the first tempering is performed at a relatively high temperature T1 and then the second tempering is performed at a relatively low temperature T2, it is possible to achieve both high strength and high toughness at a high level. This is thought to be because the newly formed martensite during the cooling process after the first tempering is appropriately tempered during the second tempering. EXAMPLES

[0060] (Examples 1 to 6, Comparative Examples 1 to 5) [1. Sample preparation] 50 kg of steel having the chemical composition shown in Table 1 was melted. The resulting steel ingot was hot forged to produce a bar having a diameter of 20 mm. Test pieces were cut from the bar, and then quenched and tempered. The quenching conditions were 950°C for 1 hour followed by oil quenching. The tempering conditions are: (a) Hold at 600-700°C for 3 hours, then air cool (temper once), or (b) Hold at 700-800°C for 3 hours, cool to room temperature, then hold at 600-700°C for another 3 hours, then air cool (tempered twice). It was decided.

[0061] 2. Test Method 2.1. Hardness The Rockwell hardness (C scale) of each sample after tempering was measured. The evaluation criteria were as follows: "○": Rockwell hardness is 27HRC or higher. "△": Rockwell hardness is 22HRC or more and less than 27HRC. "X": Rockwell hardness is less than 22HRC.

[0062] [2.2. Absorbed energy] The absorbed energy was evaluated using a 2 mm V-notch Charpy impact test. The evaluation criteria are as follows: "○": Absorbed energy is 50J or more. "△": Absorbed energy is 15J or more and less than 50J. "X": Absorbed energy is less than 15J.

[0063] [3. Results] The results are shown in Table 1. The composition of each sample is also shown in Table 1. From Table 1, the following can be seen.

[0064] (1) The hardness was low in all of the twice-tempered materials of Comparative Examples 1 to 4. This is believed to be because the formation process and type of carbides changed due to the small amount of Mo and / or Nb. (2) The absorbed energy is low in both the first-tempered and second-tempered materials of Comparative Example 5. This is believed to be due to the relatively large amount of δ-ferrite.

[0065] (3) The once-tempered and twice-tempered materials of Examples 1 to 5 all had a hardness of 22 HRC or more and an absorbed energy of 15 J or more. (4) The twice-tempered materials of Examples 2, 3, and 6 had a hardness of 27HRC or more and an absorbed energy of 50 J or more. This is believed to be because the δ-ferrite phase was relatively reduced by optimizing the balance of the components.

[0066] [Table 1]

[0067] Although the embodiment of the present invention has been described in detail above, the present invention is not limited to the above embodiment, and various modifications are possible without departing from the gist of the present invention. [Industrial Applicability]

[0068] The martensitic stainless steel according to the present invention can be used for fuel injection system parts of automobiles, shafts for ships, aircraft parts, and the like.

Claims

1. 0.10≦C≦0.25 mass%, 0.10≦Si≦1.00mass%, 0.10≦Mn≦1.50 mass%, 1.00≦Ni≦3.00mass%, 15.28≦Cr≦17.50mass%, 0.01≦Mo≦0.40mass%, 0.01≦Nb≦0.30 mass%, and 0≦V≦0.50mass% The balance is Fe and unavoidable impurities. A martensitic stainless steel that satisfies the following formula (1). Mo+2Nb+V≧0.08mass%…(1) However, when V is not included, the calculation is performed assuming V=0 in formula (1).

2. 0.01≦V≦0.50mass% The martensitic stainless steel according to claim 1 .

3. The martensitic stainless steel according to claim 1 or 2 is used. Hardness is 27HRC or more, Absorbed energy is 50J or more Martensitic stainless steel components.

4. A first step of producing a material made of the martensitic stainless steel according to claim 1 or 2; The material is A c3 A second step of quenching from a temperature equal to or higher than the solidus temperature; A third step of tempering the material after quenching; A fourth step of finish-machining the tempered material to obtain a martensitic stainless steel member; A method for manufacturing a martensitic stainless steel member comprising the steps of:

5. The third step comprises: (a) 400° C. or higher c3 or performing tempering at a temperature T below the (b) A c1 A point or above c3 Temperature below point T 1 The first tempering is performed at 300° C. or more. c3 Temperature below point T 2 (<T 1 ) A process of performing a second tempering The method for producing a martensitic stainless steel part according to claim 4, further comprising the steps of:

Citation Information

Patent Citations

  • High-strength and high-toughness large martensitic stainless steel ring forged piece and manufacturing method thereof

    CN112442634A

  • 110ksi grade high strength corrosion resistant martensitic stainless steel pipe

    JP1994299301A

  • Ink jet printing ink and ink jet printing method

    JP1995026180A

  • Stainless steel with high corrosion resistance and high strength

    JP1999229093A

  • Martensitic stainless steel

    JP2005344184A